Modelagem de procedimentos cirúrgicos para tratamento do hematoma subdural agudo - Faria, Alessandro Rodrigues (2013)
Some types of brain trauma with bleeding in the subdural space cause the Acute Subdural Hematoma (ASDH). The treatment is the surgical procedure called a decompressive craniotomy (DC), with a wide opening of the dura mater. The prognoses are discouraging because of high morbidity / mortality. The process of rapid intradural decompression causes severe cerebral extrusion, resulting in edema and ischemia. Neurosurgeons sociated with mechanical engineers, both from the Federal University of Uberlândia, proposed the method called Basal Vertex craniotomy with dural fenestration (BVCDF), in which are made multiple small incisions in the dura mater, for gradually decrease the intracranial pressure. Minimizes the effect of large deformations generated in brain structures. The analyzes of these techniques are hampered because the biological tissue is anisotropic, inhomogeneous, and possesses non-linear relationship between the stress field and strain field. The aim of this study was to evaluate the procedures DC and BVCDF modeling using living tissue integrated numerical finite element models simulating the brain environment and evaluating the biomechanical behavior. Both procedures were also qualitatively evaluated through in vitro approach. In the process BVCDF was observed not only a smaller value of total displacement in lines of dura mater and hematoma, as well as smaller value of maximum principal stress. The increase in the number of fenestrations improves the flexibility of the dura mater.